The Interest rate elasticity of aggregate consumption: a time varying parameter approach - Christian Starck (Bank of Finland, 1990)
The aim of this note is to examine whether the empirically documented positive interest rate elasticity of aggregate consumption in Finland is an artefact due to the previously widespread credit rationing. The aim is carried out using a novel time varying parameter approach and data from the period 1960 - 1989. The empirical evidence lends further support for a positive interest rate elasticity of aggregate consumption. The elasticity seems to have increased over time, especially in recent years. To some extent, this mirrors a gradual easening up of credit rationing, which has been particularly rapid in recent years.
URN:NBN:fi:bof-201908061354
Keywords: 330